Informed choice or guessing game? Understanding caregivers' perceptions and use of infant formula labelling. Issue 2 (27th November 2018) - Malek, Lenka; Fowler, Hazel; Duffy, Gillian; Katzer, Lisa
Abstract: Objective: Although breast-feeding is the recommended way to feed an infant, a safe and nutritious substitute for breast milk is needed for infants who are not breast-fed. Labelling information on infant formula (IF) products aims to enable caregivers (who have already made the decision to use IF) to make informed product choices. Yet, there is limited data on how caregivers understand and use the information provided on IF packaging. The present study aimed to increase understanding of caregivers' interpretation and use of the following label elements on IF products: the nutrition information statement; the ingredients list; and statements around nutrition content and health claims. Design: Qualitative data were obtained from twenty-one focus group discussions. To enable comparison of findings by education level and ethnicity, focus group participants were homogeneous with respect to educational attainment (Australian groups) or ethnic background (New Zealand groups). Setting: Focus groups were conducted in metropolitan and regional areas of Australia and New Zealand. Participants: Caregivers ( n 136) of formula-fed infants. Results: Framework analysis revealed that caregivers commonly experience difficulties when using labelling information, particularly when trying to identify and understand key differences between products. Moreover, comparing products can be a complex task regardless of education level and ethnicity. Conclusions: Further research is required to determine the most effective strategies for meeting information needs of caregivers and allowing easier identification and understanding of product differences. This is especially important given that the vast range of IF products across large price ranges in the market adds to the complexity of purchase decisions.